MoCA in five Indian languages: A brief screening tool to diagnose dementia and MCI in a linguistically diverse setting. (7th September 2022) - Kaul, Subhash; Paplikar, Avanthi; Varghese, Feba; Alladi, Suvarna; Sharma, Meenakshi; Dhaliwal, R. S.; Goyal, Sheetal; Saroja, Aralikatte Onkarappa; Arshad, Faheem; Divyaraj, Gollahalli; Ghosh, Amitabha; Iyer, Gowri K.; et al.
Abstract: Introduction and Objectives: Early dementia diagnosis in low and middle‐income countries (LMIC) is challenging due to limited availability of brief, culturally appropriate, and psychometrically validated tests. Montreal Cognitive Assessment (MoCA) is one of the most widely used cognitive screening tests in primary and secondary care globally. In the current study, we adapted and validated MoCA in five Indian languages (Hindi, Bengali, Telugu, Kannada, and Malayalam) and determined the optimal cut‐off points that correspond to screening for clinical diagnosis of dementia and MCI. Methods: A systematic process of adaptation and modifications of MoCA was fulfilled. A total of 446 participants: 214 controls, 102 dementia, and 130 MCI were recruited across six centers. Results: Across five languages, the area under the curve for diagnosis of dementia varied from 0.89 to 0.98 and MCI varied from 0.73 to 0.96. The sensitivity, specificity and optimum cut‐off scores were established separately for five Indian languages. Conclusions: The Indian adapted MoCA is standardized and validated in five Indian languages for early diagnosis of dementia and MCI in a linguistically and culturally diverse population. Key points: Montreal Cognitive Assessment (MoCA) is a widely used brief cognitive screening test for detecting dementia and mild cognitive impairment (MCI) globally. Due to the socio‐demographic and linguistic diversity that prevails in India, it is essential to establish brief screening tools and norms that are culturally and linguistically appropriate to diagnose dementia and MCI at community and clinical levels. The MoCA was adapted and validated in five Indian languages (Hindi, Bengali, Telugu, Kannada, and Malayalam). The diagnostic accuracy of Indian version of MoCA was excellent with good sensitivity and specificity in diagnosing dementia and MCI. The adapted and validated Indian version of MoCA can identify cognitive decline and contribute to clinical, research and rehabilitative efforts to reduce burden of dementia in the country.